Hubungan Sikap Caring Perawat Terhadap Kepatuhan Kontrol Pengobatan Pasien TB Paru Di Poli DOTS - Ricky Annas; Saiful Gunardi; Bambang Suryadi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Caring is an important aspect that must be carried out by a nurse in the practice of providing nursing care. In general, caring is defined as an ability to be dedicated to others, to provide supervision by showing attention, feelings of empathy for others, feelings of love and love that must be done in providing nursing care. The purpose of this study was to determine whether or not there is a relationship between the caring attitude of nurses towards compliance with treatment control of pulmonary TB patients. This study is a quantitative study with a cross sectional approach. This sampling technique uses purposive sampling. Statistical test analysis used is chi-square using SPSS computer program. Results: The results of the bivariate test obtained a p-value of 0.033 is smaller than 0.05, which means that there is a relationship between the caring attitude of nurses towards compliance with treatment control of pulmonary TB patients. There is a relationship between the caring attitude of nurses towards compliance with treatment control of pulmonary TB patients.